A formação pedagógica do docente universitário nas instituiçoes gaúchas - Campagnolo, Franciele Wozniak (2015)
The central theme of this thesis is the pedagogical training of university teaching and aims to identify and analyze admission policies and the programs of continued formation off the university teachers offered by the Rio Grande do Sul universities. The work development starts with a historical overview on the Brazilian university and its (un)concern teacher training, especially with the preparation of the teachers for the exercise of university teaching since its inscription. Later we approach the university teaching in all its complexity, dialogue on issues such as the constitution of teacher identity, the forms of admission to higher academic environment, the nature of university teaching and qualified for the work in higher teaching. Thirdly are presented and analyzed some empirical data showing the initiatives that the gaucha s Universities are developing for the teaching qualifications of its educators, both on the admission as the provision of continued education programs. From 19 public and private universities Gaucho invited to participate in this research, 13 institutions has collaborated in sending information through a questionnaire. The received data were analyzed both in quantitative aspect through graphics, as in the qualitative of the documents made available by the institutions. The conclusions point out that the concern with the pedagogical training of university professors in the interior of the institutions is still very low, despite several advances wich were expressed in the analyzed documents